Identification of novel competitive antagonists for Histamine H1 receptor in Malaysian kelulut honey - Feng, Tan wei; Raihana Zahirah, Edros; Dong, RuiHai (Universiti Putra Malaysia Press, 2025)
Current breakthroughs in molecular docking approaches have significantly contributed to discovering novel antagonists that competitively bind to histamine H1 receptor (H1R), thereby inhibiting histamine-mediated reactions. A reliable antagonist must possess a superior binding affinity with H1R compared to histamine while having the ability to be efficiently absorbed and traverse the intestinal barrier for systemic circulation. The consideration of human intestinal absorption (HIA) provides an extension for comprehending ligands' bioavailability before engaging in docking studies. In this study, the Brain Or IntestinaL EstimateD permeation method (BOILED-Egg) model was utilized to predict the HIA of the ligands, followed by molecular docking to target the H1R with compounds presented in Malaysian Kelulut honey that are impenetrable to the blood-brain barrier (BBB-) by using a virtual screening tool, Pyrx. The findings highlighted the importance of specific residues, including ASP 107, TYR 108, SER 111, and TYR 431, in H1R, as they interact with histamine within the binding spaces, demonstrating strong intermolecular forces. Among 69 BBB- compounds, Polydatin (PD), Sophoflavescenol, and Dendrocandin B exhibited favorable results in docking studies with H1R, indicating their potential to be used as competitive antagonists in treating allergic symptoms. A more promising candidate can be nominated to develop optimal antagonists by addressing absorption properties and binding affinity perspectives.